Theater artists making theatre with no theater Spring 2020 - Callaghan, Sheila 1973-; Miller, Kelly; Miroshnik, Meg (Tripwire Harlot Press, an imprint of Savage Candy Productions, 2020)
During the early stages of the 2020 pandemic, theater-makers across the United States were faced with the devastating reality that their profession had disappeared overnight. As a means of coping, Sheila Callaghan, Meg Miroshnik, and Kelly Miller (founding members of the feminist collective The Kilroys) sent out a call to their peers to consider what "theatre with no theater" might look like. They reached out to writers, directors, literary managers, composers, artistic associates-- basically any theater artist whose email they could dig up. They were immediately flooded with over 140 submissions in various artistic genres: Illustrations, poetry, photographs, collage, screen caps, shopping lists, monologues, etc. The result is an eclectic collection that reflects the absurdity, humor, impossibility, and grief inherent in making "theatre" at a time when live performance as we know it does not exist. Each singular piece in this volume provides a deeply intimate look at the emotional status of its creator during lockdown
Keywords: Pandemie; COVID-19; Theater; Acting; Théâtre / Aspect social; Théâtre et politique; Anthologie